Past, present, and future research on self-service merchandising: A co-word and text mining approach - Muñoz-Leiva, F.; Rodríguez-López, M. E.; Liébana-Cabanillas, F.; Moro, S. (European Journal of Marketing, 2021)
Purpose This study aims to discern emerging trends and provide a longitudinal perspective on merchandising research by identifying relationships between merchandising-related subdomains/themes. Design/methodology/approach This study sourced 657 merchandising-related articles published since 1960, from the Scopus database and 425 from Web of Science. After processing and normalizing the data, this study performed co-word and thematic network analyses. Taking a text mining approach, this study used topic modeling to identify a set of coherent topics characterized by the keywords of the articles. Findings This study identified the following merchandising-related themes: branding, retail, consumer, behavior, modeling, textile and clothing industry and visual merchandising. Although visual merchandising was the first type of merchandising to be used in-store, only recently has it become an emerging topic in the academic literature. There has been a further trend over the past decade to understand the adoption of simulation technology, such as computer-aided design, particularly in supply chain management in the clothing industry. These and other findings contribute to the discussion of the merchandising concept, approached from an evolutionary perspective. Research limitations/implications The conclusions of this study hold implications at the intersection of merchandising, sectors, new technologies, research methodologies and merchandising-practitioner education. Research trends suggest that, in the future, virtual reality and augmented reality using neuroscientific methods will be applied to the e-merchandising context. Practical implications The different dimensions of merchandising can be used to leverage store managers’ decision-making process toward an integrated store-management strategy. In particular, by adopting loyalty merchandising tactics, the store can generate emotional attachment among consumers, who will perceive its value and services as unique, thanks to merchandising items designed specifically with that aim in mind. The stimulation of unplanned purchases, the strategic location of products and duration of each merchandising activity in the store, the digitalization of merchandising and the application of findings from neuroscience studies are some of the most relevant practical applications. Originality/value This study provides the first-ever longitudinal review of the state of the art in merchandising research, taking a holistic perspective of this field of knowledge spanning a 60-year period. The work makes a valuable contribution to the development of the marketing discipline.